What are the cognitive risks associated with vitamin B12 deficiency in the elderly?. Issue 6 (June 2017) - Beck, Robert A.
Abstract : EVIDENCE‐BASED ANSWER : Whether serum vitamin B12 levels in older adults are associated with cognitive changes is unclear. However, elevated levels of methylmalonic acid, a B12 metabolite that reflects low vitamin B12 function, are more consistently associated with cognitive decline (SOR: B, systematic reviews of longitudinal studies).